Americae Sive Novi Orbis, Nova Descriptio - Ortelius, Abraham, 1527-1598 (Ortelius, Abraham 1527-1598, 1565)
16th century Copper engraving handcolored with watercolor. Full color. Relief shown pictorially. Printed in lower left corner in cartouche: "Americae Sive Novi Orbis Nova Descriptio." Written in pencil along top on verso: "America - Ortelius 1579." Printed on verso: “Novus Orbis.” First line of text on verso: “Totum hoc hemisphaerium…” Printed in bottom right corner on verso: “2.” Many distinct geographic features characterize this map. The Pacific Ocean, for example, appears "very narrow" and New Guinea is shown as "due south of California." ("Americae sive Novi Orbis, Nova Descriptio"). The eastern coasts of the Americas are shown with "amazing accuracy: the coast of Brazil is only 3 degrees too far east, the position of Hispaniola is absolutely accurate, and Newfoundland is just 8 degrees too far west." In contrast, the western coasts are distorted. Chile, Peru and California are shown as far too west, thus making both continents "too broad." Moreover, Chile seems to bulge out from South America (Burden, 51-2). Evidence from Cartier's exploration of the St. Lawrence and Spanish exploration in Mexico and the Californian coast appear within this map as well. For example, Coronado's exploration is seen in the naming of Ceuola, Tiguex and Quivira, although Quivira is depicted in the far northwest of North America instead of the Great Plains (Ermen, 11). "Chili" is shown in this map as a city and Santiago, though founded in 1541, is not shown. On the other hand, a key to numbered cities in Peru is shown in Patagonia. The Rio de la Plata is depicted with an "exaggerated width and numerous isles" (Klemp, map 15). Of note, the "mythical kingdom" of "Anian" is shown in the Northwest. Illustrations include a few small ships sailing eastward in the Pacific and Atlantic Oceans and a whale in the South Atlantic. Scale: c.a. 1:38,000,000. Abraham Ortelius (1527-1598) was a cartographer and publisher. He set up a business as a book dealer and map painter in Antwerp. He traveled a great deal, making his business successful by developing a large network of contacts around Europe. In 1564 he published a world map in eight sheets, marking the start of a long career in map publishing (Moreland and Bannister, 98). In 1570, Ortelius published the “first modern uniform atlas,” the Theatrum Orbis Terrarum (1570) (Tooley, 476). Having combined a large collection of maps from various European cartographers, he had them engraved to a standard size (Moreland and Bannister, 98). He also commissioned Frans Hogenberg to create cartouches and illustrations for these maps, following the popular style of the Flemish Renaissance (Klemp, map 15). Multiple editions of this highly successful and influential atlas were published in many languages up to 1612. Of note, Ortelius credited other cartographers. Ortelius’s other works include: “Egypt” (1565), “Asia” (1567), “Spain” (1570) and “Roman Empire” (1571) (Tooley, 476). This map is perhaps the “most famous and easily recognizable” maps of the New World from this period (Burden, 51). In the creation of the map, Ortelius either copied greatly from Mercator’s “Great World Map” of 1569 or used many of the same sources as a number of similarities arise between the two maps. As Ortelius and Mercator were good friends, it may be likely that they shared a lot of information with each other (Burden, 51). Klemp notes that the shape of South America and the “river systems” in both maps appear similar such as the Maragnon River running parallel to the Amazon. The extended shape of the Rio de la Plata is also similar to Mercator’s work and place names in South America are all the same (map 15). Of note, the map displays a “striking contrast between the known, and therefore fairly correctly and minutely drawn areas.and the still unknown” (Ermen, 11). Several versions of this map exist including the first printed in 1570 and two later plates produced, one in 1579 and one in 1587, showing no bulge at Chile. This particular map is printed from the 1579 plate in which ships are shown heading east and the border is significantly thinner than in the 1570 version (Burden, 51-2; Tooley, “Identification…”, 320-4). Source(s): “Americae sive Novi Orbis, Nova Descriptio.” University of Virginia Library. “An Exhibition of Maps and Navigational Instruments, on View in the Tracy W. McGregor Room, Alderman Library, University of Virginia July 10 to September 26, 1995.” 2008. Burden, Philip D. “The Mapping of North America: A List of Printed Maps 1511-1670.” Rickmansworth, England: Raleigh Publications, 1996. Ermen, Eduard Van. “The United States in Old Maps and Prints. Wilmington, DE: Atomium Books, Inc., 1990. Goos, John. “The Mapping of North America: Three Centuries of Map-making 1600-1860.” London: Wellfleet Press, 1990. Klemp, Egon, ed. “America in Maps: Dating from 1500 to 1856.” New York: Holmes and Meier Publishers, 1976. Lowery, Woodbury. “The Lowery Collection: A Descriptive List of Maps of the Spanish Possessions within the Present Limits of the United States, 1502-1820.” Washington, D.C.: Government Printing Office, 1912. Moreland, Carl and David Bannister. “Antique Maps: A Collector’s Handbook.” New York: Longman Group, Ltd., 1983. Portinaro, Pierluigi and Franco Knirsch. "The Cartography of North America 1500-1800." New York: Facts on File, Inc., 1987. Skelton, R. A. “Decorative Printed Maps of the 15th to 18th Centuries.” London: Spring Books, 1965. Tooley, Ronald Vere. “Identification of the Maps of America in the Various Editions of the Theatrum of Ortelius.” In “The Mapping of America.” Ed. by Ronald Vere Tooley. London: Holland Press, 1985. 320-324. --- . “Tooley’s Dictionary of Mapmakers.” Hertfordshire: Map Collector Publications Limited, 1979.